PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA CAHAYA RESTO & CAFÉ DI KECAMATAN PANYABUNGAN KOTAKABUPATEN MANDAILING NATAL - Riski khairani; Vebri Sugiharto; Rizka Ar Rahmah (BORJUIS: JURNAL OF ECONOMY, 2025)
This research aims to determine the influence of product quality on consumer purchasing decisions at Cahaya Resto & Café in Panyabungan District, Mandailing Natal Regency. In the culinary business, food quality in terms of taste and presentation is a very important factor. Food quality such as taste and appearance aspects reflect the company's success in the eyes of consumers. The quality of the product being marketed is the core of consumer assessment of the product purchased in order to obtain maximum benefit value. For manufacturers, good product quality means that the product is in demand by consumers so that it produces profits both in terms of sales and company image. Purchasing decisions by a consumer involve considerations to determine whether or not it is appropriate to purchase a product by going through various alternative product choices that best suit the desired needs. This research aims to determine the influence of product quality on purchasing decisions at Cahaya Resto & Café. This research uses quantitative research methods with a sample size of 100 Cahaya Resto & Cafe consumers with a sampling technique using random sampling technique using the Lemeshow formula. The data collection technique uses a Likert scale questionnaire. The data analysis technique uses simple linear regression using the SPSS Version 22 program consisting of validity and reliability tests, classical assumption tests (normality tests), hypothesis tests (partial tests and coefficient of determination tests). The research results show that product quality (X) influences purchasing decisions (Y) with a calculated t value of 8.726 > 1.66055 (thitung > ttable) with a significance of 0.000 < 0.05 so that Ha is accepted. Then the results of the coefficient of determination test obtained an R Square value of 0.437 which shows that the ability of product quality (X) in explaining purchasing decisions is 43.7% while 56.3% is explained by other factors that are outside the model and cannot be detected in the research.